Employee Happiness: A Critical Ingredient for Organizational Success, Evidence from Small and Medium Enterprises (SMEs) - Muzvidziwa, Rutendo Faith; Nyasha, Mapira (International Journal For Research In Business, Management And Accounting, 2019)
The research sought to assess the impact of employee happiness on organizational success. The research was carried in the form of a case study, in which a sample of 160 employees from a population of 301 employees was used. Purposive sampling procedure was employed in selecting elements from a population of 301employees. Questionnaires and interviews were used in triangulation to collect data on the sample. After analyzing the collected data, the study unearthed that happiness and organizational success go hand in hand as happy and satisfied individuals are relatively more successful in the workplace compared to their unhappy peers. The study recommended that organizations must treat employees as internal customers and make sure that they are always smiling.